The influence of tactical formation on physical and technical match performance in male soccer: A systematic review - Forcher, L.; Forcher, L.; Wäsche, H.; Jekauc, D.; Woll, A.; Altmann, S. (International Journal of Sports Science & Coaching, 2023)
The number of investigations that specifically address the influence of formation on soccer performance has increased in recent years. Since there is no overview that summarizes these effects, this systematic review aims to synthesize the available literature on the effects of tactical formation on physical and technical match performance. According to the PRISMA 2020 guidelines, a systematic search was performed (Databases: PubMed and Web of Science). Studies were included, if they reported any physical (e.g., sprinting distance) or technical (e.g., number of passes) match performance parameters and compared at least two different formations. The study outcomes were synthesized descriptively. The effect of formation on physical performance was investigated in ten studies while three studies investigated the effect on technical performance (11 studies included). The studies revealed that formation has an effect on the physical and technical match performance of soccer players both in a team and at a positional level. On a team level, smaller differences were observed for formations that are similar in the number of players in each playing position (i.e., 4-5-1, 4-2-3-1). Furthermore, physical match performance was higher in formations with three defenders (e.g., 3-5-2) in comparison to formations with four defenders (e.g., 4-4-2). On a positional level, all positions were affected in a similar way by formation. Therefore, formation affects the physical and technical match performance of soccer players and if the playing position is also considered, the results become even more meaningful. The studies were very heterogeneous regarding their methodology (i.e., parameters, sample size). The findings can help coaches to design their training programs and to prepare the players for a specific positional role depending on the tactical formation.